Early Protein Inadequacy Is Associated With Longer Intensive Care Unit Stay and Fewer Ventilator‐Free Days: A Retrospective Analysis of Patients With Prolonged Surgical Intensive Care Unit Stay. Issue 1 (3rd November 2017) - Yeh, D. Dante; Fuentes, Eva; Quraishi, Sadeq A.; Lee, Jarone; Kaafarani, Haytham M. A.; Fagenholz, Peter; Butler, Kathryn; DeMoya, Marc; Chang, Yuchiao; Velmahos, George
Abstract: Background: Failure to provide adequate nutrition in the intensive care unit (ICU) may be particularly harmful for patients with prolonged critical illness. We hypothesized that early nutrition inadequacy is more influential for those requiring a longer ICU stay versus those requiring a shorter stay. Methods: We enrolled 280 adult patients with prolonged surgical ICU stay who were receiving enteral nutrition for >72 hours. Subjects were divided into 2 groups: shortICU (<14 days) and longICU (≥14 days). Nutrition deficits at ICU days 3 and 7 were calculated. To investigate whether early nutrient deficit was associated with ICU length of stay (LOS), hospital LOS, 28‐day ventilator‐free days, and discharge disposition (home/rehabilitation vs death/nursing home), we performed linear and logistic regression analyses controlling for age, sex, body mass index, and APACHE II (Acute Physiology and Chronic Health Evaluation). Results: While the shortICU (n = 163) and longICU (n = 117) groups were similar in age, APACHE II, Injury Severity Score, energy/protein prescription, and enteral nutrition initiation within 48 hours, the longICU group was more commonly male (76% vs 61%, P = .007) and had higher body mass index (27.4 vs 25.6, P = .007). Significant interactions occurred: in the longICU group but not the shortICU group, protein deficits were associated with longer ICU stay and fewer 28‐day ventilator‐free days. Conclusions: Early protein deficits accumulating at ICU days 3 and 7 are associated with worse clinical outcomes among patients requiring longer ICU stays. Additional studies are required to confirm these findings.